2021
DOI: 10.1186/s12934-021-01623-1
|View full text |Cite
|
Sign up to set email alerts
|

Augmented peroxisomal ROS buffering capacity renders oxidative and thermal stress cross-tolerance in yeast

Abstract: Background Thermotolerant yeast has outstanding potential in industrial applications. Komagataella phaffii (Pichia pastoris) is a common cell factory for industrial production of heterologous proteins. Results Herein, we obtained a thermotolerant K. phaffii mutant G14 by mutagenesis and adaptive evolution. G14 exhibited oxidative and thermal stress cross-tolerance and high heterologous protein production efficiency. The reactive oxygen species (ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Previously, we isolated a robust P. pastoris mutant, which exhibited thermal and oxidative co-stress tolerance. In addition, the robust mutant expressed an up to 2.5-fold higher level of heterologous protein than the WT [19]. To determine whether this phenomenon could also occur in the expression of other proteins, a green fluorescence protein (GFP) was expressed in the robust mutant and its WT.…”
Section: Improved Heterologous Protein Expression Ability In the Robust Mutant Under Methanol Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we isolated a robust P. pastoris mutant, which exhibited thermal and oxidative co-stress tolerance. In addition, the robust mutant expressed an up to 2.5-fold higher level of heterologous protein than the WT [19]. To determine whether this phenomenon could also occur in the expression of other proteins, a green fluorescence protein (GFP) was expressed in the robust mutant and its WT.…”
Section: Improved Heterologous Protein Expression Ability In the Robust Mutant Under Methanol Inductionmentioning
confidence: 99%
“…The robust mutant was previously evolved by adaptive laboratory evolution [19]. Both the robust mutant and its WT expressed a recombinant protein lipase encoded by RCL gene and tightly regulated by the methanolinducible promoter P AOX1 .…”
Section: Strain and Plasmid Constructionmentioning
confidence: 99%
“…Adaptive evolution‐derived mutant (G14) of Komagataella phaffii was found to be thermotolerant with reduced lipid peroxidation and ROS levels, owing to bigger peroxisomes in G14 and thus, presenting the enhanced oxidative stress response. In addition, augmented activity and expression of peroxisomal catalase was also observed in the G14 (Lin et al, 2021).…”
Section: Evolutionary Basis For Multiple Stress Conditionsmentioning
confidence: 93%
“…Interestingly, the phenomenon that the inner cell wall thickens happened in a lager yeast which exhibited a multiple stress tolerance [74]. Fascinatingly, in our research on P. pastoris, it was also found that the environmental stress tolerance was increased, and the inner cell wall became thicker [75]. Interestingly, the CWI pathway is not the only way to maintain cell wall integrity.…”
Section: Cwi Pathwaymentioning
confidence: 71%
“…This process is achieved mainly by trehalose, UPS, and autophagy antioxidants to scavenge cellular ROS and eliminate oxidative stress. Especially, in our previous work, we found that high temperature induced OSR and HSR simultaneously in a heat-sensitive Pichia pastoris strain [39].…”
Section: Intracellular Accumulation Of Denatured Proteins and Reactive Oxygen Species (Ros) That Can Be Induced By Most Environmental Strmentioning
confidence: 81%